Incremental generation of abductive explanations for tactical behavior - Wagner, T.; Bogon, T.; Elfers, C. (CEUR Workshop Proceedings, 2007)
According to the expert literature on (human) soccer, e.g., the tactical behavior of a soccer team should differ significantly with respect to the tactics and strategy of the opponent team. In the offensive phase the attacking team is usually able to actively select an appropriate tactic with limited regard to the opponent strategy. In contrast, in the defensive phase the more passive recognition of tactical patterns of the behavior of the opponent team is crucial for success. In this paper we present a qualitative, formal, abductive approach, based on a uniform representation of soccer tactics that allows to recognize/explain the tactical and strategical behavior of opponent teams based on past (usually incomplete) observations.